DEPENDENCE OF CLINIC INDICATORS FROM LEVEL OF SYSTEMIC INFLAMMATION IN PATIENTS WITH PSORIATIC ILLNESS - Yemchenko, Y.A.; Іщейкін, К.Є.; Kaydashev, I.P. (World of Medicine and Biology, 2014)
On the basis of study of 40 patients with uncomplicated plaque psoriasis of moderate severity with concomitant metabolic syndrome shown association clinical and laboratory parameters of the level of systemic inflammation, which is important for therapies aimed at preventing the development of clinical exacerbation of psoriasis and the extension of the period of remission.
Keywords: psoriasis; metabolic syndrome; indicators of systemic inflammation